(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
تنتشر إبرة العجوز الأزميرية في سورية، وتم لأول مرة دراسة بعض الجوانب البيولوجية والسلوكية المتعلقة بها. يتميز سلوك التزاوج بتكراره أكثر من مرة مع حركات خاصة يقوم بها الذكر لجذب الأنثى، ويستمر لقاء الذكر بالأنثى بين 60 ـ 80 دقيقة، تضع الأنثى البيض عدة مرات في حياتها ( 3 ـ 5 مرات )، ويبلغ متوسط عدد البيض للأنثى الواحدة 54 بيضة، تستمر فترة حضانة البيض 17 يوماً بالمتوسط على درجة حرارة الغرفة. تمر الحشرة بأربعة أعمار في طور الحورية، لتصل إلى طور الحشرة الكاملة في فترة زمنية مدتها 71 يوماً بالمتوسط، مدة أعمار الحورية الأربعة من العمر الحوري الأول إلى العمر الرابع 18، 13، 16، و24 يوماً بالمتوسط على التوالي. تم تحديد بعض المقاييس المورفولوجية لأعمار الحورية المختلفة وهي طول الجسم وطول القرون الشرجية وعدد عقل قرن الاستشعار. بلغ طول الجسم للأعمار الحورية الأربعة من الأول إلى الرابع 4,6 مم، 9,3 مم، 15,2 مم، 18,2 مم على التوالي، بينما بلغ طول الأنثى البالغة 21,5 مم وطول الذكر 23,5 مم. وصل طول القرون الشرجية لأعمار الحورية الأربعة من الأول إلى الرابع 1,6 مم، 2,3 مم، 3,1 مم، 4,5 مم،على التوالي، للأنثى 5 مم والذكر 7.3 مم. بلغ عدد عقل قرون الاستشعار 8، 10، 10، 11، 12 أيضاً على التوالي. The dermapterous Forficula smyrnensis is spread in Syria. Some biological and morphological aspects were studied. The mating behavior is distinguished by repetition with special movment that the male does to attract the female. The meeting between male and female lasts 60 – 80 minutes. The female lays eggs several times in its whole life ( 3 – 5 times). The female fecundity is 54 eggs. The eggs hatch after 17 days at room temperature. The insect passes four nymphls instars to reach adult in 71 days respectively. The four nymphls stages from the first to the fourth age follow a sequence of 18, 13, 16, and 24 days on average. Some morphological paramerters for the different nymphls instars were determined: they were body, cerci length and number of the antenna segments. The body length of the four nymphls instars was 4.6 m.m, 9.3 m.m, 15.2m.m, 18.2 m.m; and body length of female and male was 21.5mm., 23.5 mm. respectively. The cerci length for the four nymphls instars was 1.6 m.m, 2.3 m.m, 3.1 m.m, and 4.5 m.m. The cerci length of female and male was 5mm., 7.3mm. respectively. The number of the antenna segments was 8, 10, 10, 11, for nymphls instars and 12 for adults.